New therapeutic approaches and novel alternatives for organophosphate toxicity. (July 2018) - Katz, Francine S.; Pecic, Stevan; Schneider, Laura; Zhu, Zhengxiang; Hastings-Robinson, Ashley; Luzac, Michal; Macdonald, Joanne; Landry, Donald W.; Stojanovic, Milan N.
Graphical abstract: Highlights: Previously unreported non-oxime reactivators have been discovered. These compounds have been optimized through SAR studies. Compounds have been identified that increase AChE activity and stimulate the enzyme. Inhibition of AChE by OPC can be prevented by pre-incubation with compounds. Dual reactivators were active on both AChE and BuChE. Abstract: Organophosphate compounds (OPCs) are commonly used as pesticides and were developed as nerve agents for chemical warfare. Exposure to OPCs results in toxicity due to their covalent binding and inhibition of acetylcholinesterase (AChE). Treatment for toxicity due to OPC exposure has been largely focused on the reactivation of AChE by oxime-based compounds via direct nucleophilic attack on the phosphorous center. However, due to the disadvantages to existing oxime-based reactivators for treatment of OPC poisoning, we considered non-oxime mechanisms of reactivation. A high throughput screen of compound libraries was performed to discover previously unidentified reactivation compounds, followed by studies on their analogs. In the process, we discovered multiple non-oxime classes of compounds, the most robust of which we have already reported [1]. Herein, we report other classes of compounds we identified in our screen that are efficient at reactivation. During biochemical characterization, we also found some compounds with other activities that may inspire novel therapeutic approaches to OPC toxicity. Specifically, we found compounds that [1] increase the rate of substrate hydrolysis by AChE and, [2] protect the enzyme from inhibition by OPC. Further, we discovered that a subset of reactivator compounds recover activity from both AChE and the related enzyme butyrylcholinesterase (BuChE). We now report these compounds, their activities and discuss how each relates to therapeutic approaches that would provide alternatives to traditional oxime-based reactivation.